Pengaruh Work Life Balance terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Mediasi pada Perumda Tirta Bhagasasi Cabang Bekasi Kota - Rifdah Amara Sari,; Henry Eryanto,; Maulana Amirul Adha, (Student Scientific Creativity Journal, 2026)
The purpose of this study is to identify the impact of Work Life Balance on Employee Performance, both directly and through Work Motivation as an intermediary variable. This study uses a survey method with a quantitative approach. The population in this study includes all employees in the agency studied. The sampling technique applied is a saturated sampling technique, which means all members of the population are used as respondents, with a total of 125 employees. For data analysis, this study utilizes Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), which is processed using SmartPLS software. The data analysis process involves examining the measurement model, analyzing the structural model, and testing hypotheses for both direct and indirect effects. The research findings indicate a positive and significant direct effect between (1) Work Life Balance and Employee Performance (β = 0.311; p = 0.000). However, no significant direct effect was found between (2) Work-Life Balance and Work Motivation (β=-0.044; p=0.767) and (3) Work Motivation and Employee Performance (β=0.162; p=0.210). Furthermore, the test results for the indirect effect showed that (4) Work-Life Balance did not significantly impact Employee Performance through Work Motivation (β=-0.007; p=0.787), thus Work Motivation did not function as a mediating variable.